MODEL INTENSI PENCARIAN INFORMASI DAN INTENSI PEMBELIAN - Muhammad Dharma Tuah Putra Nasution (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2016)
Lenovo company derived from China has successfully acquired IBM in the United States.Lenovo has a superior notebook that was selected as